2015
DOI: 10.2147/dddt.s83067
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and antioxidant effects of ghrelin in an experimental glaucoma model

Abstract: Damage to retinal ganglion cells due to elevation of intraocular pressure (IOP) is responsible for vision loss in glaucoma. Given that loss of these cells is irreversible, neuroprotection is crucial in the treatment of glaucoma. In this study, we investigated the possible antioxidant and neuroprotective effects of ghrelin on the retina in an experimental glaucoma model. Twenty-one Sprague–Dawley rats were randomly assigned to three groups comprising seven rats each. The rats in the control group were not opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…To further clarify the protective effect of Qcn on RGCs under COHT, we performed TUNEL and survivin staining on retinal cryosections at 2 weeks after COHT. Consistent with previous reports (Can et al, 2015 ), we found a significant increase in TUNEL-positive cells in the retinal GCL of retinas with COHT compared with those in the NC group (Figures 4A,B ). However, the number of TUNEL-positive cells was significantly reduced by two-fold when Qcn was administered ( p < 0.01).…”
Section: Resultssupporting
confidence: 93%
“…To further clarify the protective effect of Qcn on RGCs under COHT, we performed TUNEL and survivin staining on retinal cryosections at 2 weeks after COHT. Consistent with previous reports (Can et al, 2015 ), we found a significant increase in TUNEL-positive cells in the retinal GCL of retinas with COHT compared with those in the NC group (Figures 4A,B ). However, the number of TUNEL-positive cells was significantly reduced by two-fold when Qcn was administered ( p < 0.01).…”
Section: Resultssupporting
confidence: 93%
“…The extent of TUNEL staining was scored semiquantitatively as 0 (none), 1 (light), 2 (medium), and 3 (intense) [24]. …”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of TUNEL staining was made based on the extent of the staining of apoptotic cells. The extent of TUNEL staining was scored semiquantitatively as 0 (none), 1 (light), 2 (medium), and 3 (intense) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The correlation between ghrelin and eye diseases has also been reported. Can found that exogenous ghrelin treatment could significantly reduce intraocular pressure in rats [ 25 ]. However, Eraslan et al found that the expression level of ghrelin in aqueous humor of glaucoma patients was significantly lower than that of normal people [ 26 ].…”
Section: Discussionmentioning
confidence: 99%